An Improved Efficiency of Solar Photo Voltaic System Applications by Using DC-DC Zeta Converter - Veerendra, A. S.; M. R., Mohamed; M. H., Sulaiman; K., Peddakapu (Springer, 2020)
This study investigates on how a DC-DC Zeta converter act as intermediate among SPV and VSI, in which it drags the maximum power from the solar photo voltaic (SPV) system and to drive a BLDC motor connected to a water pumping system application. Here INC-MPPT (Incremental Conductance Maximum Power Point Tracking) method is utilized smartly to control the zeta converter in order to drive brushless DC (BLDC) motor smoothly. Soft starting current prevents the influence of peak starting current on the BLDC motor windings. The fundamental frequency of Electronic computational from the BLDC motor is used to avoid the voltage source inverter losses. The proposed converter is also suitable to increase the voltage of DC link connected to the VSI. The major benefit of this configuration is designed and modelled in such a way that even under dynamic conditions, the performance of a solar photovoltaic application is not affected. The suggested system is developed by using MATLAB/Simulink software